A Journal-Based Replication of "Being Chosen to Lead" - Allan Drazen; Anna Dreber; Erkut Y. Ozbay; Erik Snowberg (Center for Economic Studies and ifo Institute (CESifo), 2019)
Recent large-scale replications of social science experiments provide important information on the reliability of experimental research. Unfortunately, there exist no mechanisms to ensure replications are done. We propose such a mechanism: journal-based replication, in which the publishing journal contracts for a replication between acceptance and publication. We discuss what we learned from a proof-of-concept journal-based replication at the Journal of Public Economics. Our experience indicates that journal-based replication would be relatively straightforward to implement for laboratory experiments.
Keywords: A11; A14; C18; C92; 330; replication; reliability; experiments; journal-based replication